Cellular Activation in the Immune Response of Sarcoidosis - Zissel, Gernot (Seminars in Respiratory and Critical Care Medicine, 2014)
Sarcoidosis is a chronic granulomatous disorder characterized by an accumulation of lymphocytes and macrophages in the alveoli. Ultimately, long-lasting, nontreated disease results in a distortion of the microarchitecture of the lower respiratory tract. Our current understanding of its pathogenesis is that several sequential immunological events finally resulting in granuloma formation are involved: (1) dependent on a susceptible genetic background described by a variety of functional polymorphisms (2) the exposure to one or several still elusive antigen(s), leads to (3) an activation of macrophages, (4) an attainment of T cell immunity against the antigen(s) mediated by antigen processing and presentation by macrophages, and finally to (5) induction of granuloma formation. In this article, a detailed review on cellular and molecular mechanisms underpinning the sarcoid granulomatous lesion will be given. The important role of alveolar macrophages, T lymphocytes, regulatory T cells, and various cytokines/chemokines in orchestrating the induction, evolution, and immunoregulation of the sarcoid granulomatous/fibrotic lesions will be underscored. Although an etiological agent for sarcoidosis has not been identified, plausible “sarcoid antigens” including mycobacterial antigens such as mKatG or ESAT-6, antigens from Propionibacterium acnes, or even self-antigens will be discussed. It is possible that not one single causative agent exists but several germs, microbial products, or inorganic substances might induce pathogenetic mechanisms leading to a disease called sarcoidosis.
Keywords: sarcoidosis; granuloma; sarcoid antigens; macrophages; antigen presentation; T lymphocytes; immunoregulation